2009
DOI: 10.1245/s10434-009-0637-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Conversion from Nonmalignant to Malignant Diagnosis After Surgical Excision of Breast Papillary Lesions

Abstract: In this cohort, 9.21% of preoperative nonmalignant papillary lesions were converted to malignant diagnosis after surgery. Atypical lesions and patients aged 45 years or older were significant factors associated with such conversion. Surgical excision should be considered for papillary lesions of breast, especially for patients with the identified risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…In a cohort study by Cheng et al [16], 9.21% of preoperative nonmalignant papillary lesions were converted to malignant diagnosis after surgery. Atypical lesions and patients aged 45 years or older were significant factors associated with such conversion.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort study by Cheng et al [16], 9.21% of preoperative nonmalignant papillary lesions were converted to malignant diagnosis after surgery. Atypical lesions and patients aged 45 years or older were significant factors associated with such conversion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other researchers have supported selective excision in cases of atypia or in the presence of risk factors. [2][3][4]9,[13][14][15][16]18,[29][30][31][32][33] Table 4 shows the published data on papillomas confirmed by core needle biopsy and subsequent surgical excision and their upgrade rates to malignancy. These studies reported their rates of upgrade from benignity on core needle biopsy to malignancy and papilloma with atypia after surgical excision.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[4][5][6][7][8][9][10][11][12] Some recent investigators have suggested the use of selective surgical excision for benign papillomas without atypia after considering clinical and radiologic factors or supported conservative management. 4,7,[13][14][15][16][17][18] Prediction of clinical and radiologic factors associated with an upgrade to atypia or malignancy will be very helpful for both clinicians and radiologists.…”
mentioning
confidence: 99%
“…Moreover in some studies [9,12,14,32,33,35,45] guidance method, type of CB and needle gauge were not specified.…”
Section: Papillary Lesions With Epithelial Atypiamentioning
confidence: 99%